Mapping and Validation of Major Quantitative Trait Loci for Resistance to Northern Corn Leaf Blight Along With the Determination of the Relationship Between Resistances to Multiple Foliar Pathogens of Maize (Zea mays L.) - Ranganatha, Hosahally Muddrangappa; Lohithaswa, Hirenallur Chandappa; Pandravada, Anand (Frontiers in Genetics, 2021)
Among various foliar diseases affecting maize yields worldwide northern corn leaf blight (NCLB) is economically important. The genetics of resistance was worked out to be quantitative in nature thereby suggesting the need for detection of QTL to initiate effective marker aided breeding strategies. From the cross CML153 (susceptible) x SKV50 (resistant), the 344 F2:3 progenies were derived and screened for their reaction to NCLB during the rainy season of 2013 and 2014. Identification of QTL affecting resistance to these diseases was carried out using the genetic linkage map constructed with 194 polymorphic SNPs and the disease data recorded on F2:3 progeny families. Three QTL for NCLB resistance were detected on chromosomes 2, 5 and 8 with the QTL qNCLB-8-2 explaining highest phenotypic variation of 16.34 per cent followed by qNCLB-5 with 10.24 per cent. QTL for resistance to sorghum downy mildew (SDM) and southern corn rust (SCR) were also identified from one season phenotypic data and co-location of QTL for resistance to three foliar diseases was investigated. QTL present in the chromosome bins 8.03, 5.03, 5.04 and 3.04 for resistance to NCLB, SDM and SCR were co-localized indicating their usefulness for pyramiding of quantitative resistance to multiple foliar pathogens. Marker assisted selection was practiced in the crosses CM212 × SKV50, HKI162 × SKV50 and CML153 x SKV50 employing markers linked to major QTL on chromosomes 8, 2 and 10 for NCLB, SDM and SCR resistance, respectively. The populations were advanced to F6 stage to derive multiple disease resistant inbred lines. Out of 125 lines developed, 77 lines were tested for their combining ability and 39 inbred lines exhibited high general combining ability with acceptable level of resistance to major diseases.